A multi-scale pooling convolutional neural network for accurate steel surface defects classification - Fu, Guizhong; Zhang, Zengguang; Le, Wenwu; Li, Jinbin; Zhu, Qixin; Niu, Fuzhou; Chen, Hao; Sun, Fangyuan; Shen, Yehu (Frontiers in Neurorobotics, 2023)
Surface defect detection is an important technique to realize product quality inspection. In this paper, we develop an innovative multi-scale pooling convolutional neural network to accomplish high accuracy steel surface defect classification. The model was built based on SqueezeNet, and experiments were carried out on the NEU noise-free and noisy testing set. Class activation map visualization proves that the multi-scale pooling model can accurately capture the defect location at multiple scales, the defect feature information at different scales can complement and reinforce each other to obtain more robust results. Through T-SNE visualization analysis, it is found that the classification results of this model have large inter-class distance and small intra-class distance, indicating that this model has high reliability and strong generalization ability. In addition, the model is small in size (3MB) and runs at up to 130FPS on an NVIDIA 1080Ti GPU, making it suitable for applications with high real-time requirements.